ChemInform Abstract: A Direct and General Method for the Reductive Alkylation of Tertiary Lactams/Amides: Application to the Step Economical Synthesis of Alkaloid (‐)‐Morusimic Acid D. Issue 5 (4th February 2014) - Xiao, Kai‐Jiong; Wang, Yu; Huang, Ying‐Hong; Wang, Xiao‐Gang; Huang, Pei Qiang
Abstract A full account on previously published studies as well as their application to an improved synthesis of title compound (IX) is presented.